2015
DOI: 10.1175/bams-d-13-00290.1
|View full text |Cite
|
Sign up to set email alerts
|

The Deep Convective Clouds and Chemistry (DC3) Field Campaign

Abstract: DC3 brought together simultaneous measurements of storm kinematics, structure, electrical activity, and chemistry to improve our knowledge of how thunderstorms affect the chemical composition of the troposphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
251
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 194 publications
(258 citation statements)
references
References 74 publications
6
251
0
1
Order By: Relevance
“…Iyer et al (2016) reported a binding enthalpy of −70.5 kJ mol −1 for I − (HAc) and −106.8 kJ mol −1 for I − (HFo). The binding enthalpies are reported here as negative values, indicating an exothermic process and opposite to the NIST nomenclature for ion-molecule reactions (Bartmess, 2017). They correlated the sensitivities of Lee et al (2014) to binding energy and theorized the binding enthalpy for an analyte in an I − cluster could be used to predict its sensitivity.…”
Section: Resultsmentioning
confidence: 67%
“…Iyer et al (2016) reported a binding enthalpy of −70.5 kJ mol −1 for I − (HAc) and −106.8 kJ mol −1 for I − (HFo). The binding enthalpies are reported here as negative values, indicating an exothermic process and opposite to the NIST nomenclature for ion-molecule reactions (Bartmess, 2017). They correlated the sensitivities of Lee et al (2014) to binding energy and theorized the binding enthalpy for an analyte in an I − cluster could be used to predict its sensitivity.…”
Section: Resultsmentioning
confidence: 67%
“…The first polarized imaging nephelometer used for field measurements employed a wide-angle lens and charge-coupled device (CCD) to record the scattering phase function under two orthogonal linear polarization conditions at three wavelengths (473, 532, and 671 nm) and derive both the phase function and degree of linear polarization across the visible spectral region (Dolgos and Martins, 2014;Espinosa et al, 2017). This instrument was deployed on the NASA DC8 aircraft for the Deep Convective Clouds and Chemistry (DC3) campaign in 2012 (Barth et al, 2015) and the Studies of Emissions and Atmospheric Composition, Clouds and Climate Coupling by Regional Surveys (SEAC 4 RS) mission in 2014 (Toon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we report on observations of frozen-drop aggregates and frozen-drop chain aggregates made in the upper regions of several midlatitude thunderstorm anvils over the continental United States (US) during the Deep Convective Clouds and Chemistry (DC3; Barth et al, 2012) experiment. Our results suggest that these types of aggregates are common in the upper levels of these storms and, together with individual frozen droplets, can dominate the particle types in the upper anvil.…”
Section: Introductionmentioning
confidence: 99%